Forms of the Earth and Urban Forms - Giuseppe Tupputi (Agathón)
The relationship between the forms of Earth and the forms of the cities has ancient origins. Over the centuries, many settlements were born following the recognition of spatial vocations based inside the geographical forms, thus exalting the natural features of a specific territory. During the last century in Italy the Urban Design Theory dealt with these themes by trying to define the syntax of urban construction in relation to the forms of physical geography. In this sense, the projects for the Magliana quarters in Rome, by Saverio Muratori, and the project for Monteruscello, by Agostino Renna, can be considered as paradigmatic examples, because they represent an attempt to define settlements principles that correspond to the geomorphologic characters of the territory. The proposed paper intends to analyse these projects, in particular through the method of the critical drawing, identifying different scales of representation, each of which offers the possibility of investigating some specific structuring processes of urban form.